2019
DOI: 10.1021/acs.biomac.9b00206
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembling ELR-Based Nanoparticles as Smart Drug-Delivery Systems Modulating Cellular Growth via Akt

Abstract: This work investigates the physicochemical properties and in vitro accuracy of a genetically engineered drug delivery system based on elastin-like block recombinamers. The DNA recombinant technics allowed us to create this smart complex polymer containing bioactive sequences for internalization, lysosome activation under acidic pH and blockage of cellular growth by a small peptide inhibitor. The recombinant polymer reversibly self-assembled, when temperature was increased above 15°C, into nanoparticles with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 60 publications
(137 reference statements)
1
16
0
Order By: Relevance
“…It is also possible to design di-block ELPs containing a hydrophobic, low-transition temperature block and a hydrophilic, high-transition temperature block, which form nanoparticles at physiologic temperatures [15]. These constructs were used for chemotherapy and anti-cancer peptide delivery [16,17], ocular drug delivery [18], and immunotherapy [19], among others. If the transition temperature is tuned just above body temperature, ELPs can be used as carriers for thermally targeted drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible to design di-block ELPs containing a hydrophobic, low-transition temperature block and a hydrophilic, high-transition temperature block, which form nanoparticles at physiologic temperatures [15]. These constructs were used for chemotherapy and anti-cancer peptide delivery [16,17], ocular drug delivery [18], and immunotherapy [19], among others. If the transition temperature is tuned just above body temperature, ELPs can be used as carriers for thermally targeted drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Our therapeutic construct included an Akt-in peptide, which inhibits the phosphorylation of the protein kinase Akt at serine 473. 28,35 This step is key for Akt cytoplasmic activation and its kinase activity regulating multiple signaling pathways. 25 Moreover, other bioactive sequences were added in order to allow the controlled release of the therapeutic inhibitor in the target cells.…”
Section: Resultsmentioning
confidence: 99%
“…32−34 In the present work, we have studied the effect of a novel therapeutic treatment based on smart self-assembling ELR NPs for controlled and precise drug delivery of an Akt inhibitor to patient-derived pancreatic cancer cells. Although these ELR NPs were previously characterized and studied in breast and colorectal in vitro cancer cell cultures, 35 this is the first time these NPs have been evaluated as a novel strategy for PDAC therapy, in patient-derived models, as a first step toward the development of a novel therapy. Therefore, we developed an advanced nanocarrier for controlled drug delivery, which could be a promising treatment for pancreatic cancer in combination with chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, tumor-specific promoters provide a safe and effective strategy for designing gene-therapy systems that can be adapted for use with various tumors or delivery systems. To date, ELRs and other polymers widely used as non-viral vectors, such as poly-lysine (PLL), polyethylenimine (PEI), polyethyleneglycol (PEG), chitosan, poly(lactic-co-glycolic acid) (PLGA), or poly(2-dimethylaminoethyl methacrylate) (pDMAEMA) [20], have found increasing applications in biomedicine due their inherent biocompatibility and smart properties [21][22][23][24][25][26][27][28][29]. A previous study showed the ability of ELRs joined to functional peptides to be used as delivery vectors with no cellular effects in vitro [30].…”
Section: Breast Cancer Is the Most Commonly Occurring Cancer Diagnosementioning
confidence: 99%